IN THE ERA OF GLOBALIZATION: THE ETERNAL TRADITION OF PILGRIMAGE TO THE SACRED SITES AND MAUSOLEUMS OF THE TASHKENT OASIS (Scientific journal of the Fergana State University, 2025)
Visiting holy places and graves is one of the ancient rites of the peoples of Central Asia. It is worth noting that today the topic of pilgrimage has again become one of the most pressing. As a result of the influence of globalization and the development of the tourism industry, the number of traveling pilgrims increases every еar. Our homeland is also famous throughout the world for its great scientists, scientists and saints. This, in turn, is of great importance in the development of pilgrimage tourism in our country. In preparing this article, the tomb of Sheikh Umar Vali, one of the famous shrines of the Tashkent oasis, was chosen as the object of research. The pilgrimage sites of the Tashkent oasis have local features that distinguish them from other regions of the republic, with their history, architectural solutions, and pilgrimage rites of the local population. Pilgrimage rituals are especially well preserved in the mountainous and hilly areas of the oasis. The following questions were identified during the study: what are the main reasons for the revival of pilgrimage traditions in the modern world and what is the uniqueness of the shrine of Sheikh Umar Wali? In preparing the article, data from field studies conducted in the Tashkent oasis were widely used.